The production of money how to break the power of bankers - Pettifor, Ann. (London Verso, 2017)
What is money, where does it come from, and who controls it? In this accessible, brilliantly argued book, leading political economist Ann Pettifor explains in straightforward terms history's most misunderstood invention: the money system. Pettifor argues that democracies can, and indeed must, reclaim control over money production and restrain the out-of-control finance sector so that it serves the interests of society, as well as the needs of the ecosystem. The Production of Money examines and assesses popular alternative debates on, and innovations in, money, such as "green QE" and "helicopter money." She sets out the possibility of linking the money in our pockets (or on our smartphones) to the improvements we want to see in the world around us"-- Provided by publisher.
Includes bibliographical references.
Keywords: Money